The Research Trends of Pharmacopuncture Therapy on Cervical Pain Caused by Traffic Accidents - Dong-young Kim; Seung-hyo Hong; Soo-yeon Han; Won-young Kim; Seo-hye Oh; Hyung-woo Lee; Hyun-su Woo (Korean Pharmacopuncture Institute, 2020)
Objectives: The purpose of this study is to comprehensively review Korean domestic stud-ies and investigate the research trends of pharmacopuncture therapy on cervical pain caused by traffic accidents. Methods: Domestic studies between February 1999 and May 2020 from four Korean databases were searched with combinations of keywords 'cervical pain', 'traffic accident', 'whiplash injury', and 'pharmacopuncture'.Results: 17 studies were selected for review, including 7 randomized controlled trials, 5 retrospective observational studies, 3 case reports, and 2 non-randomized controlled trials. Each study was reviewed by published year, study type, types of pharmacopuncture solu-tions, selected acupuncture points, dosage of pharmacopuncture solutions, frequency of treatment, concurrent treatments, outcome measurements, and the effectiveness of phar-macopuncture therapy. The results are as follows: (1) It showed that the total number of published studies had increased slightly in the last 10 years compared to the previous de-cade. (2) The pharmacopuncture solutions used in the studies were in the following order: Bee-Venom (蜂毒), Jungsongouhyul (中性瘀血), Hwangryunhaedoktang (黃連解毒湯) and Soyeom (消炎). Frequently used acupuncture points were GB20, GV21, A-shi point, GV16, EX-B2, and SI15 in order. (3) The most commonly used total injection dosage was 1.0 cc at a time, and the frequency of treatment was twice a week. (4) Concurrent treatments such as acupuncture, herbal medication, physical therapy and Chuna manual therapy were per-formed in all 17 studies. (5) Pharmacopuncture therapy showed positive effects on cervical pain caused by traffic accidents in all 17 studies reviewed.Conclusion: Pharmacopuncture therapy was effective in cervical pain caused by traffic ac-cidents in all 17 studies selected. Further studies will be needed using more larger scales and more objective data to confirm the effectiveness of pharmacopuncture therapy and to generalize its application.